Analisis Kelayakan Bisnis Pada UMKM Mie Ngonah - Agus Sutardi; Ajeng Reni Razmayanti; Meira Purnama Rizki; Rizky Syaifullah; Shapdani Anggara Priyadi; Yumita Sari Dianti (Lembaga Pengembangan Kinerja Dosen, 2024)
This article or writing aims to find out